Pola SegregasiKarakter KetahananTanaman Kedelai(Glycine max [L]. Merrill)Terhadap Infeksi Soybean Mosaic Virus Populasi F2 Keturunan Taichung X Tanggamus - Nidya Wanda; Maimun Barmawi; Hasriadi Mat Akin; Nyimas Sa’diyah (Jurnal Penelitian Pertanian Terapan, 2015)
This study aims to determine the pattern of segregation character soybean plant resistance to infection SMV and other agronomic characters as well as many genes that play a role in the inheritance of these traits in the F2 populations from crosses Taichung x Tanggamus follow of Mendel ratio or a modification of expectations and knowing the number of crosses. This research was conducted at the Laboratory LapanganTerpadu Faculty of Agriculture, University of Lampung from September 2013 until January 2014, and then continued in the laboratory observations Seed and Plant Breeding, University of Lampung. Propagation of virus carried in Kampung Baru, Bandar Lampung. This research uses experimental design without repetition with a single treatment design nested structured data is analyzed using the chi-square test for the suitability of the normal distribution and chi-squared test to test the of Mendel ratio and modifications . The results of this study indicate the character frequency distribution of plant height, grain weight per plant soybeans F2 generation from crosses Taichung x Tanggamus normal spread, while the frequency distribution for character flowering age, harvesting, healthy seed number per plant, number of productive branches, number of pods per plants and severity of disease spread is not normal. Estimates of the number of genes that control the character of harvesting is controlled by two genes are recessive epistasis duplicate the ratio 9: 7, days to flowering follow the ratio 1: 2: 1 which is controlled by a single gene that reacts not perfect, healthy character of the number of seeds per plant followed the ratio 3: 1 and for the total character of pods per plant, number of productive branches as well as the severity of the disease follows the ratio of 13: 3. the character dikendalikanolehdua genes dominant-recessive epistasis react. There are 21 numbers belonging expectations resistant to SMV. Keywords: Soybean, segregation, resistance characteristics, and SMV.